ANALYTICAL HIERARCY PROCESS (AHP) APPROACH ON CONSUMER BUYING BEHAVIOR IN SELECTING CIGARETTES - Liando, Shella; Saerang, David P. E.; Tumbuan, Willem J. F. A (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: A cigarette is a small cylinder of finely cut tobacco leaves rolled thin in paper for smoking. Rates of cigarettes smoking very widely throughout the world and have changed considerably since cigarettes were first widely used in the mid-19 century. It keep growing the demand of cigarettes, even young people mostly like to show off using cigarettes. Regarding the circumstance above, through this research will analyze that three cigarettes in Manado (Gudang Garam (Surya), Marlboro, and Sampoerna) with the criteria that can influence consumer preferences to select a cigarette, and try to find which cigarette to meet the customers’ satisfaction the most and which criteria has influence the most people in selecting a cigarette. The result using Analytical Hierarchy Process (AHP) shows that Gudang Garam is the most preferred cigarette brand for all among the alternatives, from the seven criteria, Price and Quality is the most concerned criteria. If the price is not match with the price that consumer want, consumer will still choose the most affordable one, in this case is Gudang Garam. The two other companies may have to recheck the price that the companies have been put in the product.Keywords: Consumer Buying Behavior, Analytical Hierarchy Process